2021
DOI: 10.3390/rs13183569
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Height Variation Hypothesis with the R rasterdiv Package for Tree Species Diversity Estimation

Abstract: Forest biodiversity is a key element to support ecosystem functions. Measuring biodiversity is a necessary step to identify critical issues and to choose interventions to be applied in order to protect it. Remote sensing provides consistent quality and standardized data, which can be used to estimate different aspects of biodiversity. The Height Variation Hypothesis (HVH) represents an indirect method for estimating species diversity in forest ecosystems from the LiDAR data, and it assumes that the higher the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Firstly, the primary objective of this study was to investigate the feasibility of utilizing RGB UAV images to assess vegetation structure complexity for estimating HH and flower and bee diversity and bee abundance. Secondly, choice was guided by the findings of Tamburlin et al 72 , who, testing the HVH with LiDAR data, evaluated various LiDAR metrics (such as entropy and standard deviation of point cloud distribution, percentage of returns above mean height) for HH estimation and demonstrated that the CHM was the most effective metric to characterize vegetation HH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the primary objective of this study was to investigate the feasibility of utilizing RGB UAV images to assess vegetation structure complexity for estimating HH and flower and bee diversity and bee abundance. Secondly, choice was guided by the findings of Tamburlin et al 72 , who, testing the HVH with LiDAR data, evaluated various LiDAR metrics (such as entropy and standard deviation of point cloud distribution, percentage of returns above mean height) for HH estimation and demonstrated that the CHM was the most effective metric to characterize vegetation HH.…”
Section: Discussionmentioning
confidence: 99%
“…Torresani et al 79 , 80 tested this approach positively in different forested areas using both Airborne Laser Scanning (ALS, where the LiDAR sensor is mounted on an aircraft) and space-borne GEDI (Global Ecosystem Dynamics Investigation) LiDAR data 14 , 16 , 34 , 53 for the assessment of tree species diversity. Tamburlin et al 72 also tested the methodology in forested areas using ALS data, showing that the Canopy Height Model (CHM) is the most appropriate LiDAR metric for an accurate estimation of vegetation height heterogeneity and inference of species diversity. The approach has been used not only to assess vegetation diversity but also to estimate animal diversity, different studies showed that the variability in habitat structure has a significant effect on the bird diversity in both agricultural and forest ecosystems 2 , 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Although overstorey and understorey LiDAR returns can be successfully separated in sparsely vegetated savanna environments, the separation capabilities becomes less effective in canopies with dense and continuous architecture especially when LiDAR point density is low [ 160 , 162 ]. Canopy height models (CHM), which simulate continuous surfaces (grids) of canopy tops, have been used to solve such problem instead of directly relying on point cloud height information.…”
Section: Remote Sensing Of Savanna Woody Plant Species Diversity Usin...mentioning
confidence: 99%
“…Canopy height models (CHM), which simulate continuous surfaces (grids) of canopy tops, have been used to solve such problem instead of directly relying on point cloud height information. For example, [ 162 ] used LiDAR metrics generated from CHM to correlate Rao’s Q and Shannon diversity indices extracted from 100-m 2 plots in a Mediterranean savanna of 270 ha. Using simple linear regression, the authors reported R 2 of 0.73 for Shannon diversity index and R 2 of 0.75 for Rao’s Q.…”
Section: Remote Sensing Of Savanna Woody Plant Species Diversity Usin...mentioning
confidence: 99%
“…Recently, remote sensing and Earth observation has made significant progress with estimating various aspects of biodiversity in a standardized way at large spatial scales (Torresani et al, 2020;Tamburlin et al, 2021;Michele et al, 2018;Rocchini et al, 2022). Satellite remote sensing (hereafter SRS) has the advantage that it covers vast spatial scales, it can provide information on a variety of ecological characteristics such as vegetation distribution (e.g.…”
Section: Introductionmentioning
confidence: 99%